Balancing Climate Change Concerns and The Need for Economic Development in Uganda : A Case Study of the East Africa Crude Oil Pipeline Project - Kabre, Jonathan (University of Pretoria, 2023)
Dissertation (LLM (International Trade and Investment Law in Africa))--University of Pretoria, 2023.